Advancing Sexual Pleasure as a Fundamental Human Right and Essential for Sexual Health, Overall Health and Well-Being: An Introduction to the Special Issue on Sexual Pleasure. Issue 4 (2nd October 2021) - Coleman, Eli; Corona-Vargas, Esther; Ford, Jessie V.
Abstract: On September 11, 2021, the World Association for Sexual Health ratified a Declaration on Sexual Pleasure in its General Assembly. This declaration was a bold attempt by WAS to urge all spheres of influence in society to recognize the critical importance of sexual pleasure as a key component of sexual health and sexual rights. This special issue of the International Journal of Sexual Health (the official journal of the WAS) contains a technical document which supports the Declaration. In addition, it contains background papers that were commissioned to inform the evidence supporting the technical document and to outline the strategies for implementing the WAS Declaration on Sexual Pleasure in promoting sexual health and rights.